Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.11648/j.ijnrem.20220701.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Existing Agroforestry Practices in East Hararghe Zone Oromia, Ethiopia

Abstract: An agroforestry practice produces different benefits, which enhance household incomes and diversification of products. This study was aimed to identifying existing agroforestry practices and to identify perception behind of agroforestry practice and to identify the opportunities and major constraints related to agroforestry practices in Fedis, Kersa and Jarso Districts of the lowland, midland and highlands agro ecologies, of East Hararghe Zone, oromia, Ethiopia. The study was based on a household survey conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Wild res and droughts posed comparatively less of a threat to WEPs. Women and the youth are the main WEP collectors, which is in agreement with ndings from previous study in Ethiopia that women and children are the main gatherers of WEPs (Abdella et al, 2023 andGuzo et al, 2023). Therefore, it is important to recognize the roles that women and children play in helping to gather WEPs and in managing the WEP issue in Ethiopia (Cherenkow, 2014).…”
Section: Preference Ranking Of Factors Threatening Wepssupporting
confidence: 91%
See 1 more Smart Citation
“…Wild res and droughts posed comparatively less of a threat to WEPs. Women and the youth are the main WEP collectors, which is in agreement with ndings from previous study in Ethiopia that women and children are the main gatherers of WEPs (Abdella et al, 2023 andGuzo et al, 2023). Therefore, it is important to recognize the roles that women and children play in helping to gather WEPs and in managing the WEP issue in Ethiopia (Cherenkow, 2014).…”
Section: Preference Ranking Of Factors Threatening Wepssupporting
confidence: 91%
“…Particularly, recording and documenting the WEPs, ecosystem services, threats and status of biodiversity in Ethiopia have become imperative through studying unexplored areas of the country. Few studies on ethno-botanical of WEPs have been conducted in different regions of Ethiopia (Kidane & Kejela, 2021, Duguma, 2020, Addis et al, 2023, Abdella et al, 2023, Guzo et al, 2023; however, no ethno-botanical studies on the same have been conducted in the present study areas. Therefore, this study examined the genetic biodiversity, ecosystem services, threats and management of WEPs in South -Central Ethiopia.…”
Section: Introductionmentioning
confidence: 71%
“…From exist agroforestry practice at study area Alley cropping is the least percentage (16.7%) at both zone. In contrast in East Hararghe parkland agroforestry (58%), followed by alley cropping as hedge row intercropping (33%), homegardens (22%), multipurpose trees on farmland (19%), live fence/boundary tree planting (18%), and wind breaks (4%) were identi ed (Musa et al, 2022). In this report alley cropping the second dominant agroforestry practice.…”
Section: Agroforestry Practice In Study Areamentioning
confidence: 67%
“…Tis study showed that most farmers strongly agreed that agroforestry practices are essential for the farming community to boost farm income. Tese results were confrmed by Abdella et al [63], Diriba et al [64], and Saha et al [65], who stated that agroforestry practices helped to increase farmers' incomes in Ethiopia and Bangladesh. Similarly, most farmers had a positive perception (strongly agreed and agreed) towards the benefts of agroforestry practices in terms of creating fuelwood for household consumption and sales.…”
Section: Discussionmentioning
confidence: 94%
“…Tis is supported by the study by Saha et al [65], who found that farmers in Bangladesh had favorable opinions of agroforestry practices as a way to satisfy their fundamental needs for fuel wood. A study by Abdella et al [63] also indicated that 74% of households in Ethiopia had a positive perception of how agroforestry practices helped to produce fuelwood. Te study also revealed that most of the respondents strongly agreed (had a positive perception) that employing agroforestry practices is crucial for the agricultural community to reduce soil erosion and increase soil formation.…”
Section: Discussionmentioning
confidence: 99%